Presidential policies and the road to the second Iraq war from Forty One to Forty Three - Davis, John 1962- (Ashgate, 2006)
Examining the continuity and divergent strategies of Bush, Clinton and Bush Jr and their efforts to respond to the Iraqi threat, this essential volume provides policy makers with guidelines and prescriptions about the future of postwar Iraq with a detailed analysis of lessons learned both during the military and reconstruction phases.